Zrnate stročnice v prehrani (University of Maribor Press, 2022)
Grain Legumes in Human Nutrition. The monograph, entitled Grain legumes in human nutrition, deals with various aspects of the inclusion of grain legumes in human diet. A historical overview of the use of legumes and the factors contributing to the growing demand for their production is provided. The high nutritional value of legumes related to macronutrient composition and vitamin and mineral content is presented. Processing of legumes is the necessary step to improve the availability of nutrients and reduce the content of undesirable substances. In addition to milling and thermal treatment, nutritional value can also be improved by fermentation and sprouting. The publication describes in detail the use of soy in Asian cuisine, where it forms the basis of the daily diet. In Slovenia, more and more legume products can be found on store shelves. The great potential that legumes have in human nutrition has been recognized by many entrepreneurs and some success stories are presented in the monograph. Locally grown legumes contribute to better food security and higher quality.